Characterization And Identification & Development Of Physical Mixture Of Torsemide (Journal of Pharmaceutical Negative Results, 2023)
Innumerable problems are encountered while formulating a drug of poor water solubility into a formulation with good bioavailability. A couple of decades ago, the reason behind failures in drug development was due to poor biopharmaceutical properties such as poor water solubility of the drugs molecules. The process of new drug development can come to a standstill if the drug candidate has poor water solubility or if it is completely insoluble in water. Due to poor solubility of drugs in water, many marketed products need to be reformulated as the formulation cannot avail the desired amount of drug to the site of action. The drugs can provide relief, but the diuretics are poorly soluble in nature. So, formulating them is a tedious and difficult task. So, before formulation their solubility should be enhanced in order to increase drug availability and bioavailability simultaneously. The present research work aims to enhancing the solubility of the drug to multiple folds. Solid dispersion particularly aims at enhancing the solubility of poorly water-soluble drugs by the use of solid solubilises. A combination of solubilises can be used to enhance the solubility of the drug leading to reduction in individual concentrations of solubilises and effective enhancement of solubility of the drug. In the present study, poorly water-soluble drug, Torsemide, was the drug of choice. It was incorporated into solid dispersion using random combination of several solubilizes. The solubilizes were dissolved in water and then drug was added, a clear yellow solution was formed. The excess water was evaporated from this solution and solid dispersion was obtained which was later dried completely, pulverized and packed